Identifikasi Keberadaan Batu Apung Berdasarkan Data Georadar dan Data Geolistrik Resistivitas di Kecamatan Ampenan dan Kecamatan Sekarbela, Kota Mataram - Arsi, Sefti Dini; Farid, Muhammad; Refrizon, Refrizon (Jurnal Ilmu Fisika, 2025)
This study was conducted to identify the presence and distribution of pumice resulting from the 1257 AD eruption of Mount Samalas in the Ampenan and Sekarbela Districts of Mataram City. The research is significant because pumice serves as a volcanic indicator that greatly influences soil characteristics and the local environment. The study aims to map the distribution of pumice and to examine its subsurface dispersal, particularly in coastal areas. Georadar and geoelectric resistivity methods were employed—two geophysical techniques that measure the electrical response of the subsurface, thereby detecting changes in resistivity and conductivity indicative of volcanic material such as pumice. The results reveal that pumice is uniformly distributed at depths of 0–9 meters and is intermixed with gravel, silt, and sand. In the study area, the soil layer is predominantly sandy, likely due to its coastal location. This research underscores the importance of using geophysical methods to map the distribution of volcanic materials in shallow layers, especially in areas affected by volcanic eruptions.